Horizontal inequalities and affirmative action: An analysis of attitudes towards redistribution across groups in Africa - Arnim Langer; Frances Stewart; Maarten Schroyens (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Inequalities between ethnic or racial groups, defined as horizontal inequalities, are pervasive and persistent. They persist due to cumulative and reinforcing inequalities arising from unequal access to different types of capital. Affirmative action policies can provide promising opportunities for escaping this inequality trap. However, political support for these policies across a wide range of groups in society is crucial for introducing and maintaining them. Interestingly, little is known about the popular support for affirmative action policies and redistribution across ethnic groups, in particular in developing countries. We aim to address this lacuna by providing an overview of theories relating to attitudes towards redistribution across groups and analysing these issues empirically in Ghana, Nigeria, Kenya and Uganda.
Keywords: 330; horizontal inequalities; affirmative action; economic redistribution; ethnicity; Africa